Odpowiedzi

2009-11-27T17:20:37+01:00
(2x-5)2=4x2
4x2-25=4x2
4x2-4x2=-25
0=-2

x2+4=(x+2+2
x2+4=x2+4
x2-x2=4-4
0=0

(5+2x)(2x-5)=4x2-5
10x-25+4x2-10x=4x2+5
4x2-4x2+10x-10x=25+5
0=30


2x(8x-3)=(3-4)2
16x2-6x=9-16x2
16x2+16x2-6x=9
32x4-6x=9
26x3=9

(3x-5)(3x-5)=9x(x=1)
9x2+15x-25+9x(x=1_
9x2-9x+15x-15x-x=25
0=25

4(5x)2-(10x+4)2=0
4+25x-100x+16=0
25x-100x=0-4-15
-75x=-20
Pozdrawiam:)
2009-11-27T17:33:06+01:00
A)(2x-5)=4²
4x²+25=4x²
25≠0
równanie sprzeczne
b)x²+4=(x+2)²
x²+4=4+x²
0=0
równanie nieoznaczone
c) (5+2x)(2x-5)=4x²-5
10x-25+4x²-10x=4x²-5
-20≠0
równani sprzeczne
d) 2x(8x-3)=(3-4x)²
16x²-6x=9-12x+16x²
6x=9 /:3
x=3
e) (3x-5)(3x+5)=9x(x-1)
9x²+15x-15x-25=9x²-9x
-25=-9x /:(-9)
x=2⅔
e') (3x-5)(3x+5)=9x(x+1)
9x²+15x-15x-25=9x²+9x
-25=9x /:(-9)
x=-2⅔

napisałem dla dwóch bo napisałeś (3x-5)(3x+5)=9x(x=1)

f)4(5x)²-(10x+4)²=0
4*25x²-100x²+40x+16=0
40x=-16
x=-0,4

Mam nadzieje że dobrze
Jeśli nie rozumiesz napisz do mnie